Demo: End-to-end open-source location-based augmented reality in 5G - Soros, Gabor; Nilsson, John; Wu, Nan; Shane, Jennifer; Kadlubsky, Alina (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
The vision of an augmented reality (AR) cloud is about an enhanced version of the real world extended by persistent, location-anchored digital objects. We present a fully open source, end-to-end solution for placing, storing, and re-discovering geo-anchored AR contents in the real world. We advanced various components of the Open Spatial Computing Platform (OSCP) and deployed it in a 5G testbed. We created a new OSCP reference client in Unity and built representative demo applications that allow virtual objects to persist throughout space and time. We created a data collector application for spatial mapping, and we connected the OSCP with an open-source visual positioning system. Furthermore, we created tutorials on the setup to foster its adoption in the scientific community as a platform for location-based AR experiments.